Answer:
The most basic fact about triangles is that all the angles add up to a total of 180 degrees. The angle between the sides can be anything from greater than 0 to less than 180 degrees. The angles can't be 0 or 180 degrees, because the triangles would become straight lines.
Step-by-step explanation:
basic only
Answer:
6. E
7. D
8. 5,-8,34
Step-by-step explanation:
A. Parallel to the y-axis and passes through the point (3,5)
For it to be parallel to the y-axis, what this means is that it has an x-intercept and no y intercept.
So what this means is that x = 3 is our line so E is correct
B. Perpendicular to the y-axis means it is parallel to the x-axis
It means is has no x intercept and thus its x value at any point in time is zero
So the equation is y = -5
or simply y + 5 = 0 which means D is correct
C. It is parallel to the line 5x -8y + 12 = 0
Thus: 8y = 5x + 12
dividing both sides by 8
y = 5x/8 + 12/8
y = 5x/8 + 3/2
y = 5x/8 + 1.5
Comparing this with the general equation of a straight line ;
y = mx + c
where m is that slope, this means that 5/8 is the slope of the line
Mathematically if two lines are parallel, they have equal slopes.
So we can say the slope of the other line too is 5/8
Now to find the equation of the other line, we can use the point-slope method
y-y1 = m(x-x1)
where (x1,y1) in this case is (-2,3)
So we have;
y-3 = m(x-(-2))
y-3 = 5/8 (x + 2)
8(y-3) = 5(x + 2)
8y -24 = 5x + 10
5x + 10 + 24 -8y = 0
5x -8y + 34 = 0
So A, B, C = 5, -8, 34
there are 0.125 cups inside 1 fluid ounces
144 / 0.125 = 1152 (divide because you are trying to figure out how many of the volumes of the mold can fit inside the 144 fluid ounces
You can fill 1152 molds with 144 fluid ounces
The system is:
i) <span>2x – 3y – 2z = 4
ii) </span><span>x + 3y + 2z = –7
</span>iii) <span>–4x – 4y – 2z = 10
the last equation can be simplified, by dividing by -2,
thus we have:
</span>i) 2x – 3y – 2z = 4
ii) x + 3y + 2z = –7
iii) 2x +2y +z = -5
The procedure to solve the system is as follows:
first use any pairs of 2 equations (for example i and ii, i and iii) and equalize them by using one of the variables:
i) 2x – 3y – 2z = 4
iii) 2x +2y +z = -5
2x can be written as 3y+2z+4 from the first equation, and -2y-z-5 from the third equation.
Equalize:
3y+2z+4=-2y-z-5, group common terms:
5y+3z=-9
similarly, using i and ii, eliminate x:
i) 2x – 3y – 2z = 4
ii) x + 3y + 2z = –7
multiply the second equation by 2:
i) 2x – 3y – 2z = 4
ii) 2x + 6y + 4z = –14
thus 2x=3y+2z+4 from i and 2x=-6y-4z-14 from ii:
3y+2z+4=-6y-4z-14
9y+6z=-18
So we get 2 equations with variables y and z:
a) 5y+3z=-9
b) 9y+6z=-18
now the aim of the method is clear: We eliminate one of the variables, creating a system of 2 linear equations with 2 variables, which we can solve by any of the standard methods.
Let's use elimination method, multiply the equation a by -2:
a) -10y-6z=18
b) 9y+6z=-18
------------------------ add the equations:
-10y+9y-6z+6z=18-18
-y=0
y=0,
thus :
9y+6z=-18
0+6z=-18
z=-3
Finally to find x, use any of the equations i, ii or iii:
<span>2x – 3y – 2z = 4
</span>
<span>2x – 3*0 – 2(-3) = 4
2x+6=4
2x=-2
x=-1
Solution: (x, y, z) = (-1, 0, -3 )
Remark: it is always a good attitude to check the answer, because often calculations mistakes can be made:
check by substituting x=-1, y=0, z=-3 in each of the 3 equations and see that for these numbers the equalities hold.</span>